Treaties, trenches, mud, and blood - Hale, Nathan, 1976- (New York : Amulet Books, 2014)
In 1914, the world's biggest countries (and some of its smallest, too) were gearing up for a massive fight. Land, history, geography -- each country came to war for different reasons and with different resources. But most ended up the same: sending their young men to fight for their lives in the mud, on the sea, and in the air, in a conflict that would eventually claim more than 9 million lives.
Includes bibliographical references.
Ages 8-12.
Keywords: World War, 1914-1918 -- Juvenile literature; World War, 1914-1918 -- Comic books, strips, etc; World War, 1914-1918.; Cartoons and comics; Graphic novels